2003
DOI: 10.1093/humrep/deg411
|View full text |Cite
|
Sign up to set email alerts
|

Impaired ovarian blood flow and reduced antral follicle count following laparoscopic salpingectomy for ectopic pregnancy

Abstract: Ovarian function seems to be impaired after laparoscopic unilateral salpingectomy at short-term assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 33 publications
3
65
0
1
Order By: Relevance
“…12 The increase in the ovarian volume in both the groups in our study can be explained by various previous studies. Study by Elinia et al 14 showed that "a significant increase in ovarian volume was observed 6 and 12 months after TAH.…”
Section: From 1stsupporting
confidence: 75%
“…12 The increase in the ovarian volume in both the groups in our study can be explained by various previous studies. Study by Elinia et al 14 showed that "a significant increase in ovarian volume was observed 6 and 12 months after TAH.…”
Section: From 1stsupporting
confidence: 75%
“…Salpingectomy is another treatment option and most favorite surgical procedure for EP [4]. There were many studies that evaluated the impact of salpingectomy on ovarian reserve.…”
Section: Resultsmentioning
confidence: 99%
“…Salpingectomy is a surgical option for the treatment of selected patients with EP [3]. Both surgical and medical methods for EP were found to affect ovarian reserve by impairing the proliferation of the germinal cells or blood supply of the ovary [2,4]. However, recently published studies suggested that single-dose MTX in the treatment of EP is safer and may be the first treatment choice [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Additional Doppler volumetric scans with various quantitative blood-flow measures have been conducted in a variety of organs. Examples include breast (Bhatti et al 2001;Carson et al 1998, Hochmuth et al 2002, prostate (Moskalik et al 2001a(Moskalik et al , 2001bPotdevin et al 2001), uterus (Jokubkiene et al 2006), placenta (Merce et al 2005), and ovary (Chan et al 2003). Mehta et al (2004) have reviewed various studies which show the advantages of 3D ultrasound with and without contrast enhancement relative to 2D scans in the detection and staging of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%